Chemical Characterization and Pharmacological Evaluation of Phytophenols-Etodolac Mutual Prodrugs - Shah, Kamal; Krishna, Gaurav (Iraqi Journal of Pharmaceutical Sciences, 2023)
Etodolac is choice of drug for pain and inflammation but has major side effects of gastric ulcers that are due to free carboxylic group. Etodolac belongs to the chemical class of non-selective COX-inhibitor but preferentially COX-2 inhibitor. Here the ester linked mutual prodrugs of etodolac with phytophenols like vanillin, carvacrol, umbelliferone, guaiacol, sesamol and syringaldehyde were synthesized. All the prodrugs were characterized by IR-spectroscopy, 1H-NMR, 13C-NMR and mass spectrometry. Among the synthesized prodrugs, the Eto-van, Eto-umbe, Eto-sesa and Eto-syr showed improved analgesic and anti-inflammatory activity compared to etodolac. All the synthesized prodrugs showed less ulcerogenic side effects compared to etodolac.